PRESS AND LITERARY ENVIRONMENT - Amonkeldi Akhmatov (Western European Studies, 2024)
The press played an important role in the processes of the literary environment that began in the 20th century, and writers effectively used it to convey their ideas to the people. This article describes the specific aspects of the literary environment formed in Bukhara, the activities of writers, the news that entered literary processes, and the emergence of the press.
Keywords: History of Bukhara; literary environment; press